Chromosome painting of Z and W sex chromosomes in Characidium (Characiformes, Crenuchidae) - Pazian, Marlon F. [UNESP]; Shimabukuro-Dias, Cristiane Kioko [UNESP]; Pansonato-Alves, José Carlos [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Springer Nature, 2013)
Some species of the genus Characidium have heteromorphic ZZ/ZW sex chromosomes with a totally heterochromatic W chromosome. Methods for chromosome microdissection associated with chromosome painting have become important tools for cytogenetic studies in Neotropical fish. In Characidium cf. fasciatum, the Z chromosome contains a pericentromeric heterochromatin block, whereas the W chromosome is completely heterochromatic. Therefore, a probe was produced from the W chromosome through microdissection and degenerate oligonucleotide-primed polymerase chain reaction amplification. FISH was performed using the W probe on the chromosomes of specimens of this species. This revealed expressive marks in the pericentromeric region of the Z chromosome as well as a completely painted W chromosome. When applying the same probe on chromosome preparations of C. cf. gomesi and Characidium sp., a pattern similar to C. cf. fasciatum was found, while C. cf. zebra, C. cf. lagosantense and Crenuchus spilurus species showed no hybridization signals. Structural changes in the chromosomes of an ancestral sexual system in the group that includes the species C. cf. gomesi, C. cf. fasciatum and Characidium sp., could have contributed to the process of speciation and could represent a causal mechanism of chromosomal diversification in this group. The heterochromatinization process possibly began in homomorphic and homologous chromosomes of an ancestral form, and this process could have given rise to the current patterns found in the species with sex chromosome heteromorphism. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Cytogenetic; DOP-PCR; FISH; Freshwater fishes; Microdissection; Sex chromosomes; animal; centromere; Characidae; chromosome painting; classification; genetics; heterochromatin; phylogeny; polymerase chain reaction; sex chromosome; Animals; Centromere; Chromosome Painting; Heterochromatin; Phylogeny; Polymerase Chain Reaction; Sex Chromosomes; Characidium; Characidium fasciatum; Characidium gomesi; Characidium sp.; Characiformes; Crenuchidae; Crenuchus spilurus; Pisces